2013
DOI: 10.1590/s1984-82502013000300011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin analogues versus human insulin in type 1 diabetes: direct and indirect meta-analyses of efficacy and safety

Abstract: All patients with Diabetes Mellitus (DM) receive insulin therapy. In this study, we evaluated the efficacy, safety and tolerability of human insulin and insulin analogues. We performed a systematic review of the literature and a meta-analysis according to the Cochrane Collaboration methodology. In the absence of clinical studies comparing insulins, we performed a mixed treatment comparison to establish the differences between the active treatments. We included studies published from 1995 to 2010. HbA1c results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…According to the analysis by the values of Odds Ratio (OR) between the comparisons of total episodes of hypoglycemia, the meta-analysis used in this study has shown: detemir vs. (Sanches et al, 2013). It is noteworthy that the analysis performed in this study did not consider the cost of adverse reactions of the insulins.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…According to the analysis by the values of Odds Ratio (OR) between the comparisons of total episodes of hypoglycemia, the meta-analysis used in this study has shown: detemir vs. (Sanches et al, 2013). It is noteworthy that the analysis performed in this study did not consider the cost of adverse reactions of the insulins.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the cost per IU of the drug was multiplied by the mean daily dose in IU recommended for each type of insulin, and calculated per patient/year. The mean dose values assigned to each type of insulin were extracted from the studies used in the meta-analysis by Sanches et al (2013) (Anderson Jr et al, 1997;Home, 2000;Hermansen et al, 2004;Heller, Koenen, Bode, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis comparing long-acting analogues (glargine or detemir, used once daily) and NPH insulin showed no significant differences in HbA1c outcomes. However, twice-daily detemir showed a modest HbA1c benefit to NPH insulin in comparative studies (mean difference=−0.14%; 95% CI −0.21 to −0.08) 23. Direct comparisons between basal analogues and NPH insulin on patient-reported outcomes including quality of life and treatment satisfaction are lacking.…”
Section: New Insulinsmentioning
confidence: 99%